Migration Misadventures: The Challenges of Creating an Inter-Institutional Migration Plan - Jones, Laura Kathryn Nicole (Proceedings of the Wisconsin Space Conference, 2023)
Archival institution migration projects are planned data transfers from existing data formats to more accessible formats that assist in preserving transferred data, improving information retrieval, and preventing obsolescence. Various archival institutions are increasingly planning migration projects because current technology makes the process easier and more affordable than in the past. In this proceeding, I will walk through the planning stages and associated challenges of NASA’s inter-institutional migration plan, Archival Description Center Migration Plans Project, which is part of a larger reorganization of the archives’ functional area to an Enterprise program. For this project, we utilized the open-source, standards-based, web-based applications Access to Memory and Archivematica. At the current project stage, we have collaborated with archivists from seven of the eleven existing NASA archive centers. One of the goals of this Enterprise reorganization is to facilitate cross-collection search and discovery and establish cross-institution metadata standards.